Fast Facts - Peatfield, Richard; Dodick, David (Abingdon : Health Press Limited Plymouth : NBN International [Distributor], 2002)
Annotation Headache is one of the most commonly experienced medical conditions and imposes enormous economic costs. It varies widely in degree and type and can arise from very many different sources. It is crucially important that healthcare professionals understand the different diagnoses and how to distinguish the benign from the potentially life-threatening. This updated and expanded edition, written by internationally recognized authorities, provides an invaluable overview for the non-specialist physician. David W. Dodick, MD, is a neurologist at the Mayo Clinic in Scottsdale, Arizona.
Trade
Keywords: Electronic books